102 Foot Drop Assessment of Spine Surgeons's Understanding of L5 Radiculopathy vs Peroneal Neuropathy. (August 2015) - Maulucci, Christopher Michael; Madineni, Ravichandra; Ghobrial, George M.; Hannon, Michelle; Riew, K. Daniel; Harrop, James S.
Abstract : INTRODUCTION: The spine surgeon often encounters patients with a foot drop. It is the task of spine physicians to be able to determine the etiology and responsible pathological process based upon history, physical examination, electrophysiological testing, and radiographic studies. A detailed knowledge of the musculoskeletal anatomy of the lower extremity and of the peripheral nervous system is beneficial to interpret the aforementioned findings in order to arrive at an accurate diagnosis. Specifically, the spine surgeon needs to be able to identify whether a "foot drop" is the result of a central, radicular, or neuropathic etiology. Peroneal neuropathy must be differentiated from L5 radiculopathy, because the treatment strategies for each of the pathologies differ. METHODS: An Internet-based survey consisting of 9 questions was distributed to 6231 members of Arbeitsgemeinschaft für Osteosynthesefragen (AO) Spine network. The survey asked for demographic information including practice setting, years in practice, geographic location, and type of training. It also consisted of 5 questions regarding musculoskeletal anatomy, neuroanatomy, and neurophysiology of the L5 nerve root and the peroneal nerve. RESULTS: A total of 645 responses were received. Of these, 464 (72%) had all 9 questions answered and were considered as complete. Final analysis of results was based only on the 464 complete surveys. Fourteen respondents (3%) answered all anatomy questions correctly. Two hundred twenty-nine surgeons from academic institutions answered 51% of the questions correctly. Two hundred thirty-five surgeons from all other practice settings answered 44% of the questions correctly ( P = .142). There was no difference in the ability of surgeons from different geographic regions to answer the questions correctly. CONCLUSION: There may be a lack of knowledge among spine surgeons of the lumbosacral plexus and lower extremity anatomy. Medical education dedicated to the musculoskeletal system and neuroanatomy may be necessary so that gaps in knowledge may be minimized.